Season of conspiracy: Calvin, the French Reformed Churches, and Protestant plotting in the reign of Francis II (1559-60) - Benedict, Philip (Transactions of the American Philosophical Society, 2020)
Season of Conspiracy considers the March 1560 conspiracy of Amboise and subsequent plots devised later that year to remove the young King Francis II from the sway of his chief advisors of the house of Guise and improve the legal situation of France's Protestant movement. New and rediscovered evidence--most important, the long-lost testimony of a cabinetmaker engaged in the plotting from January through September--reveals the conspiracies to have been more closely linked to the network of Reformed churches within France and to John Calvin in Geneva that previously understood. The results compel a reconsideration not only of events that are often said to have constituted the first act of the French Wars of Religion, but also of Calvin's political engagement and sagacity